Development of Ag-Data Hubs and Decision Support Systems - Santos, Bruno; Teviotdale, Mark; Kumar, Shalini; Getachew, Tesfaye; Rischkowsky, Barbara A.; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
To increase the accessibility of climate-smart sheep and goat breeding and integrated interventions, a data and information platform has been developed to support data collection, storage, and analyses, creating useful information for structured decision-making within the small ruminant sector throughout Ethiopia. The tasks and activities completed to date are outlined in the following chapters. Chapter 1 provides an overview of the data structure, flow of information, and their integration to support decision-making at different levels within households, villages, and across the entire Community-based Breeding Program (CBBP) in Ethiopia. Chapter 2 describes progress to date, list of priorities to develop new functionality within Dtreo (data and information management system), and the required support to improve usage and adoption of tools within the CBBP. Chapter 3 presents a vision of the next steps of the data and information management system as an essential component to support the CBBP and AICCRA to engage a larger number of small ruminant owners throughout Ethiopia. This project was undertaken as part of a staged set of tasks to provide the necessary support to the International Center for Agricultural Research in the Dry Areas (ICARDA) for the specific small ruminant deliverables of the Accelerating the Impacts of CGIAR Climate Research in Africa (AICCRA) project in Ethiopia and Tanzania. The upgrade of platforms is required to establish the infrastructure that enables much larger data storage capability, with prompt retrieval of larger datasets, and analytic features. The project has delivered the required tasks which established an infrastructure that allows successful data collection, integration, and framework to support evaluation and data analytics to be presented to stakeholders and smallholder farmers. Smallholder farmers participating in the CBBP are supported through a platform made available to researchers and enumerators. These features will be presented to breeding cooperatives, to smallholder farmers, and commercial farmers in further stages of the project. A modern livestock data platform now underpins the CBBP progression in Ethiopia and other African countries. This project is linked to the activities associated to research activities related to deliverables of the 1.3.1: Development of Ag-Data Hubs and Decision Support Systems activity within “Accelerating the impacts of CGIAR climate research in Africa (AICCRA)”.